2020
DOI: 10.1111/cei.13497
|View full text |Cite
|
Sign up to set email alerts
|

MASP2 levels are elevated in thrombotic microangiopathies: association with microvascular endothelial cell injury and suppression by anti-MASP2 antibody narsoplimab

Abstract: The role of the lectin pathway (LP) of complement has not been explored in the thrombotic microangiopathies (TMA). We examined levels of MASP2, the effector enzyme of the LP, in three major forms of TMA and assessed the effect of the anti‐MASP2 human monoclonal antibody narsoplimab on TMA plasma‐induced activation of caspase 8 in microvascular endothelial cells. MASP2 levels were highly elevated in all TMA patients versus controls. Caspase 8 activation was suppressed by clinically releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 29 publications
0
44
0
Order By: Relevance
“…SARS-CoV-2 may directly activate the LP of complement through binding to MBL via its glycoprotein envelope spikes, as has been documented for SARS-CoV [ 9 ], and suggested by the demonstration by our group of CoV-2 envelope spike protein binding to MASP2 [ 4 ]. Multiple positive feedback loops involving complement receptor-mediated inflammatory cytokine release and interactions among leukocytes, platelets, and endothelial cells have been documented in a variety of pathologic settings [ 18 ]. Significant deposits of complement components C5b-9, C4d, and MASP2 in the pulmonary, renal, and cutaneous microvasculature of SARS-CoV-2-infected patients [ 4 , 7 ], accompanied by microthrombosis, are consistent with systemic activation of complement and related pathology.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 may directly activate the LP of complement through binding to MBL via its glycoprotein envelope spikes, as has been documented for SARS-CoV [ 9 ], and suggested by the demonstration by our group of CoV-2 envelope spike protein binding to MASP2 [ 4 ]. Multiple positive feedback loops involving complement receptor-mediated inflammatory cytokine release and interactions among leukocytes, platelets, and endothelial cells have been documented in a variety of pathologic settings [ 18 ]. Significant deposits of complement components C5b-9, C4d, and MASP2 in the pulmonary, renal, and cutaneous microvasculature of SARS-CoV-2-infected patients [ 4 , 7 ], accompanied by microthrombosis, are consistent with systemic activation of complement and related pathology.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study has shown that inhibition of MASP2 by narsoplimab can reduce thrombotic microangiopathy (TMA) plasma-mediated human microvascular endothelial cell injury. 67 …”
Section: Antibody Therapeutics Undergoing First Regulatory Review In mentioning
confidence: 99%
“…60 More recent observations report that inhibition of mannose-binding lectin-associated serine protease (MASP2), the effector enzyme of LP, may be beneficial in conditions such as thrombotic microangiopathy (TMA) post allogeneic hematopoietic stem cell transplantation (alloHSCT). 61 In general, all these proposed mechanisms share in common the dominant role of complement activationespecially through the AP pathway -in the pathophysiology of SCD. Some studies revealed elevated biomarkers of complement activation in both steady state and crisis of SCD patients or mouse models.…”
Section: Underlying Mechanisms Of Complement Activation In Scd For Thmentioning
confidence: 99%
“… 60 More recent observations report that inhibition of mannose‐binding lectin-associated serine protease (MASP2), the effector enzyme of LP, may be beneficial in conditions such as thrombotic microangiopathy (TMA) post allogeneic hematopoietic stem cell transplantation (alloHSCT). 61 …”
Section: Underlying Mechanisms Of Complement Activation In Scd For Thmentioning
confidence: 99%